Nutritional support in paediatric Crohn's disease: outcome at 12 months. (13th October 2017) - Gavin, J; Ashton, JJ; Heather, N; Marino, LV; Beattie, RM
Abstract: Aim: Paediatric Crohn's disease (CD) is associated with growth delay and poor nutritional status. Maintenance enteral nutrition (MEN) supplementation is a potential adjunct to improve growth/prolong remission. Methods: Newly diagnosed CD patients were identified. Anthropometry, treatments and outcomes were collected for 12 months following diagnosis. Data are presented as medians. Results: A total of 102 patients were identified (age = 13 years, 76% male), 58 (57%) completed exclusive enteral nutrition (EEN) as induction therapy, and 77 (75%) entered clinical remission. Following induction, 58 (57%) of all patients continued MEN and 44 (43%) consumed normal diet (ND). BMI Z ‐score increased (diagnosis‐12 months) for EEN (−1.41 to −0.21 (p = <0.0001)) and steroid groups (−0.97 to −0.11 (p = 0.001)). BMI Z ‐score increased (post induction – 12 months) for MEN (−0.62 to −0.44 (p = 0.04)) but not ND (−0.33 to −0.4 (p = 0.79)). Height Z ‐score did not increase for any treatment group over 12 months. MEN and ND group relapse rates were similar at six months, MEN = 21/58 (36%); ND = 21/44 (48%) (p = 0.24) and 12 months, MEN = 24/58 (41%); ND = 13/44 (30%) (p = 0.22). Fewer patients treated with EEN then MEN relapsed less than six months, 14 of 43 (33%), compared to patients treated with steroids then ND 16/29 (55%) (p = 0.09). Conclusion: BMI Z ‐score increased but height Z ‐score remained unchanged over 12 months for the MEN group. Use of MEN was not associated with prolonged time to relapse. Prospective studies are required to examine the utility of MEN.